2021
DOI: 10.2147/amep.s321116
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Clinical Learning Outcomes and Associated Factors Among Midwifery and Nursing Undergraduate Students of Jimma University, Ethiopia

Abstract: Background Effective achievement of clinical learning outcomes indicates the success of the clinically oriented educational program including midwifery and nursing. In contrast, studies reported poor achievement of clinical competence in different health sciences programs in the country. Thus, this study aimed to determine the status of achievement of clinical learning outcomes and associated factors among midwifery and nursing students of Jimma University, Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…But in our study, the insist was on the number of the staff, while in two other studies mostly their behaviour were important. In another study, high volume of students in the clinical learning area was positively associated with the achievement of clinical learning outcomes, 29 which is opposite to our study findings. Students in our study believed that the more students in the clinical area the harder for the instructor to manage.…”
Section: Discussioncontrasting
confidence: 99%
“…But in our study, the insist was on the number of the staff, while in two other studies mostly their behaviour were important. In another study, high volume of students in the clinical learning area was positively associated with the achievement of clinical learning outcomes, 29 which is opposite to our study findings. Students in our study believed that the more students in the clinical area the harder for the instructor to manage.…”
Section: Discussioncontrasting
confidence: 99%
“…This might be due to; students studying in private program are usually recruited when they fail to score pass-mark for regular program and most of them have engaged in other areas of work, giving less emphasis for their clinical practice. In contrast to this, students studying in post-basic program were recruited from health care institutions to upgrade their professional level and easily adapt clinical learning environment with ability to achieve the required clinical competency [ 27 ]. Students having good interaction with clinical staffs were 7 times more clinical competency as compared to those having poor interaction with working staffs, which was consistent with studies in University of Gondar and Bahir Dar [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected by using a structured questionnaire developed after reviewing relevant literature. 2,[14][15][16] The questionnaire contained four sections: socio-demographic characteristics (five questions), cognitive aspect of clinical learning (seven questions), affective aspect of clinical learning (eight questions), and psychomotor aspect of clinical learning (sixteen questions). English version questionnaire was used for data collection as both the data collectors and the respondents were considered as they can understand English in a good manner since it is the official language of instruction in the country starting from grade nine through university.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Generally, pre-and post-clinical conferences augment the relationship between clinical teachers and learners thereby creating better and deeper clinical learning opportunities which are very essential in midwifery education. 5,[14][15][16] The existing evidence, 16 and our practical observation of the clinical teaching practice in the area where this study was conducted showed that pre-and post-clinical conferences were applied poorly and the undergraduate midwifery students had a poor performance in their clinical learning. Thus, this study aimed to assess the effectiveness of pre-and postclinical conferences in improving clinical learning among third-year undergraduate midwifery students of Jimma University.…”
Section: Introductionmentioning
confidence: 99%